ADVANCEMENTS AND CHALLENGES IN PSORIASIS MANAGEMENT: EXPLORING INNOVATIVE THERAPIES, DRUG DELIVERY SYSTEMS, AND HOLISTIC APPROACHES - KOUR, TANVINDER; SINGH, AJEETPAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
The fast proliferation of skin cells that results in the production of red, scaly plaques-most frequently on the scalp, elbows, knees, and lower back-is the hallmark of psoriasis, a chronic, non-contagious skin illness. Psoriasis is generally acknowledged to be a complex illness involving immune system dysregulation and genetic predisposition; even if it’s precise origin is still unknown. Its development and exacerbation are also significantly influenced by environmental triggers, trauma, stress, and climatic circumstances. Itching, discomfort, dry skin, joint inflammation (psoriatic arthritis), and irregular nail growth are some of the clinical manifestations of psoriasis. Patients' physical, mental, social, and financial quality of life is greatly impacted by the illness, which frequently results in stigmatization, depression, and diminished capacity for day-to-day functioning. Although there are many therapeutic options available, there is no permanent cure, hence the main goals of illness management are symptom control and quality of life enhancement. Given the mounting evidence that psoriasis is a systemic inflammatory disease, understanding its comorbidities-such as diabetes and cardiovascular disease-is essential to provide patients with complete care. Biological therapies, phototherapy, non-biological systemic medications, and topical medicines are all used in modern treatment plans. Systemic and biologic medicines are essential for treating severe psoriasis, but topical therapies are the main choice for mild to moderate instances. These traditional treatments, however, are constrained by side effects, exorbitant expenses, and inconsistent patient reactions. Promising substitutes to improve therapeutic results are provided by the development of nano-carrier drug delivery systems, such as liposomes, phytosomes, niosomes, ethosomes, and transferosomes. These vesicular systems provide targeted, sustained drug release, improved bioavailability, and reduced systemic toxicity. Continued exploration and clinical validation of these innovative delivery platforms are crucial to overcoming the shortcomings of existing therapies and improving patient quality of life in psoriasis care.